2017
DOI: 10.15587/1729-4061.2017.90836
|View full text |Cite
|
Sign up to set email alerts
|

Research into technologies of obtaining grape must in the production of sparkling base wines

Abstract: Досліджено вплив технологій отримання сусла на кількісний вміст та якісний склад поверхнево-ак-тивних речовин у виноматеріалах із винограду сор-тів Сухолиманський білий і Піно Нуар. Розроблено регресійні моделі залежності хімічного складу поверхнево-активних речовин від схем відбору вино-градного сусла. Встановлено, що пінисті властиво-сті виноматеріалів визначаються компонентним складом біополімерних комплексів Ключові слова: технологія сусла, виноматеріа-ли для ігристих вин, поверхнево-активні речовини, піни… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In contrast with the results described above, most studies point to a positive influence of total polysaccharides on both foamability [22,25,26,40,42] and foam stability [28,29,50,56] ( Table 1). The relation of the molecular weight of polysaccharides and the foaming properties of wines has also been studied.…”
Section: Polysaccharidesmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast with the results described above, most studies point to a positive influence of total polysaccharides on both foamability [22,25,26,40,42] and foam stability [28,29,50,56] ( Table 1). The relation of the molecular weight of polysaccharides and the foaming properties of wines has also been studied.…”
Section: Polysaccharidesmentioning
confidence: 57%
“…Most studies indicate a positive influence of protein content on foam height in grape juices, base wines and sparkling wines [16,20,[22][23][24][25][26][27][38][39][40][41][42][43][44][45][46][47][48][49][50] (Tables 1 and 2). Some of this studies showed positive correlations between proteins and parameter HM [12,25,42,43,45,49], Peak H, and Plateau H [22].…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation